Observations of the Sea Ice Cover Using Satellite Radar Interferometry - Ronald Kwok (2004)
The fringes observed in repeat pass interferograms are expressions of surface relief and relative displacements. The limiting condition in the application of spaceborne radar interferometry to the remote sensing of the sea ice cover is the large magnitude of motion between repeat passes. The translation and rotation of ice floes tend to decorrelate the observations rendering radar interferometry ineffective. In our study, we have located three images in the high Arctic during a period when there was negligible motion between repeat observations. The fringes obtained from these images show a wealth of information about the sea ice cover which is important in atmosphere-ice interactions and sea ice mechanics. These measurements provide the first detailed remote sensing view of the sea ice cover. Ridges can be observed and their heights estimated if the interferometric baseline allows. We have observed ridges with heights greater than 4m. The variability in the phase measurements over an area provides an indication of the large scale roughness. Relative centimetric displacements between rigid ice floes have been observed. We illustrate these observations with examples extracted from the interferograms formed from this set of ERS-1 SAR images.